Memperkuat Identitas Pendidikan Multikultural pada Masyarakat Urban di MI Al Fithrah Surabaya - Ixfina, Ficky Dewi (SAP (Susunan Artikel Pendidikan), 2024)
Multicultural education becomes very important in diverse urban communities, especially in the context of Islamic schools. However, many challenges are faced in implementing multicultural values, such as the gap between teachings in school and the students social reality, as well as the limited support from parents and the community.This study aims to explore how MI Al Fithrah Surabaya strengthens the identity of multicultural education within an urban community. A qualitative approach was employed in this research, with data collection primarily through in-depth interviews, observations, and document analysis. The findings reveal that MI Al Fithrah has made efforts to integrate multicultural values into the curriculum and school activities, despite challenges such as the gap between school teachings and the social realities faced by students, as well as the limited support from parents and the community. To address these challenges, it is recommended to enhance teacher training, periodically revise the curriculum, and increase community involvement. These findings suggest that multicultural education at MI Al Fithrah has significant potential in shaping students into more tolerant individuals who are prepared to navigate diversity, although further support is needed to achieve optimal effectiveness. This study contributes to the understanding of the importance of multicultural education in Islamic schools, particularly within the context of diverse urban communities.